Determinants of pro-environmental behaviour within the university community: Insights from Islamic religiosity, risk perception, and environmental attitudes - Azizatul Lutfiah; Darihan Mubarak; Norfaizah Othman; Dini Zilali; Syaidah Fitri; Idhafiyyah Anwar; Safira Nur Auliya; Riska Annisa (Indonesian Journal of Social and Environmental Issues (IJSEI), 2026)
Pro-environmental behaviour is a crucial aspect in addressing climate change and environmental degradation, particularly in higher education, which plays a strategic role in shaping ecological awareness. This study examines the contributions of Islamic religiosity, climate change risk perception, and environmental attitudes to pro-environmental behaviour in university communities in Indonesia. Using a quantitative approach, data were collected via an online survey of 435 Muslim respondents, including students, lecturers, and administrative staff. The analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) in SmartPLS 4.0. The results show that Islamic religiosity shapes environmental attitudes and directly encourages pro-environmental behaviour. Meanwhile, climate change risk perception does not directly influence pro-environmental behaviour but rather shapes positive environmental attitudes. These findings confirm that environmental attitudes serve as a psychological mechanism linking climate risk awareness and religious values to environmental protection actions. Theoretically, this study strengthens the model of pro-environmental behaviour by integrating Islamic religiosity, climate risk perception, and environmental attitudes. In practice, these findings encourage universities to strengthen environmental education grounded in climate risk literacy and religious values.